THE PRINCIPAL'S STRATEGY IN IMPLEMENTING TIME DISCIPLINE CULTURE - Dessy Ariani Hasibuan; Zailani Zailani; Mavianti Mavianti (Proceeding International Seminar of Islamic Studies, 2022)
The aims of this study include (1) To find out the principal's strategy in cultivating time discipline for teachers and students; (2) Strict sanctions for teachers and students who cannot apply the culture of time discipline in the school; (3) The impact of implementing a culture of time discipline for school members. The approach used in this study is a descriptive qualitative method in the form of observations and interviews with the principal, as well as representatives of three teachers and students of SMP Muhammadiyah 01 Medan. From the results of the research through observations and interviews with several sources, it was found that the strategy used by the principal in cultivating time discipline was one of them by going directly to give examples to attend school early, even before the bell rang. As for the strict sanctions given by the principal to teachers and students who violate the culture of time discipline, namely in accordance with the agreement that has been written in the school's rules and regulations. Furthermore, it is known that one of the positive impacts of time discipline for school members is that teaching and learning activities become more effective. Based on the results of the study, it can be concluded that the implementation of a time discipline culture carried out by teachers and students at the school has not been effective, this is certainly caused by several inhibiting factors.Keywords: Strategy, Principal, Time Discipline.